Formulating dynamic agents operational state via situation awareness assessment - Mostafa S.A.; Sharifuddin Ahmad M.; Annamalai M.; Ahmad A.; Gunasekaran S.S. (Springer Verlag, 2023)
Decision making; Distributed computer systems; Intelligent agents; Multi agent systems; Software agents; Adjustable autonomy; Collaborative environments; Dynamic environments; Dynamic interactive systems; Layered Structures; Operational state; Real-time application; Situation awareness; Autonomous agents